Tantangan dan Peluang Pelaku Usaha UMKM menghadapi Visi Indonesia Emas 2045 - Akhadi, Iman (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to identify the challenges and opportunities faced by MSME enterpreneurs in achieving the Vision of Golden Indonesia 2045. This research employs a qualitative method through a literature study, collecting data and information from various media sources with a library study approach. These media sources include books, journals, conference proceedings, articles, and online news, which support the development of this study. The results of the study showed that the key factors challenges for MSMEs contribution toward realizing the Golden Indonesia 2045 vision include intensifying global competition, rapid advancements in digital technology and e-commerce, limited access to funding, and suboptimal human resource quality. Furthermore, shifting consumer behavior, evolving government policies, and the need to ensure business sustainability are critical factors that MSME players must proactively address. However, these challenges also present opportunities for creative and innovative MSMEs to thrive and grow. Digital technology, particularly e-commerce platforms, along with government support in the form of favorable regulations and access to financing through Fintech, creates avenues for MSMEs to expand their markets and enhance their competitiveness. Additionally, Indonesia's ongoing demographic bonus offers significant potential for boosting productivity, driven by a young generation with a strong entrepreneurial spirit